The maximum likelihood data singular locus. (March 2017) - Horobeţ, Emil; Rodriguez, Jose Israel
Abstract: For general data, the number of complex solutions to the likelihood equations is constant and this number is called the (maximum likelihood) ML-degree of the model. In this article, we describe the special locus of data for which the likelihood equations have a solution in the model's singular locus.